(untitled) (Scientific journal of the Fergana State University, 2025)
Sesame (Sesamum) is an annual and perennial plant belonging to the Sesamaceae family family of plants, oilseed. 19 types are known. Homeland - Africa. to Central Asia Imported from India. Indian sesame (S. indicum L.), a one-year cultivated type that is a spring crop in agriculture, is cultivated in India, China, South-East Asia, Africa, Iran, Central Asia and other countries.